GLIAL ABNORMALITIES IN MOOD DISORDERS - Öngür, Dost (Harv Rev Psychiatry, 2014)
Multiple lines of evidence indicate that mood disorders are associated with abnormalities in the brain's cellular composition, especially in glial cells. Considered inert support cells in the past, glial cells are now known to be important for brain function. Treatments for mood disorders enhance glial cell proliferation, and experimental stimulation of cell growth has antidepressant effects in animal models of mood disorders. These findings suggest that the proliferation and survival of glial cells may be important in the pathogenesis of mood disorders and may be possible targets for the development of new treatments. In this chapter, we will review the evidence for glial abnormalities in mood disorders. We will discuss glial cell biology and evidence from postmortem studies of mood disorders. This is not carry out a comprehensive review; rather we selectively discuss existing evidence in building an argument for the role of glial cells in mood disorders.